2015
DOI: 10.1136/vr.102834
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of perioperative analgesics by UK small animal veterinary surgeons in 2013

Abstract: Data from a survey conducted in 1996-1997 suggested a low level of perioperative analgesic administration to cats and dogs in the UK. In order to evaluate current practice and attitudes with regards to perioperative analgesic prescription, a cross-sectional survey of UK practising small animal veterinary surgeons was undertaken in spring 2013. Four thousand one hundred paper questionnaires were distributed and the survey was made available online. Seven hundred and twenty valid responses were received and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
91
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 23 publications
7
91
1
1
Order By: Relevance
“…However, cats [5/5 (100%)] were more effectively managed for pain when compared with dogs (25/57 [44%]), although these low numbers preclude drawing precise conclusions (Muir et al ). Perioperatively, cats routinely received fewer analgesics for most surgical procedures, especially opioids, when compared with dogs (Hansen & Hardie , Capner et al , Lascelles et al , Raekallio et al , Hugonnard et al , Williams et al , Hewson et al ,, Lorena et al , Perret‐Gentil et al , Hunt et al ). In contrast, a survey study performed in Brazil indicated no differences in the percentage of dogs and cats being treated with analgesics for surgical procedures (Lorena et al ), 50% of these Brazilian respondents had participated in a continuing education, master's, PhD or residency programme, which may have biased the results.…”
Section: Factors Affecting Analgesic Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cats [5/5 (100%)] were more effectively managed for pain when compared with dogs (25/57 [44%]), although these low numbers preclude drawing precise conclusions (Muir et al ). Perioperatively, cats routinely received fewer analgesics for most surgical procedures, especially opioids, when compared with dogs (Hansen & Hardie , Capner et al , Lascelles et al , Raekallio et al , Hugonnard et al , Williams et al , Hewson et al ,, Lorena et al , Perret‐Gentil et al , Hunt et al ). In contrast, a survey study performed in Brazil indicated no differences in the percentage of dogs and cats being treated with analgesics for surgical procedures (Lorena et al ), 50% of these Brazilian respondents had participated in a continuing education, master's, PhD or residency programme, which may have biased the results.…”
Section: Factors Affecting Analgesic Administrationmentioning
confidence: 99%
“…In contrast, a survey study performed in Brazil indicated no differences in the percentage of dogs and cats being treated with analgesics for surgical procedures (Lorena et al ), 50% of these Brazilian respondents had participated in a continuing education, master's, PhD or residency programme, which may have biased the results. In Canada and the UK, cats were less likely to receive perioperative analgesia for orthopaedic, abdominal and castration surgeries when compared with dogs (Hewson et al , Hunt et al ). These disparities in the prevalence of analgesic administration may be due to the differences in the perception of pain for specific procedures between species, challenges in pain assessment including failure of recognition, level of education and fear of adverse effects produced by analgesics in general (Muir et al , Lorena et al ).…”
Section: Factors Affecting Analgesic Administrationmentioning
confidence: 99%
“…Additionally, the incidence of undesirable side effects, such as vomiting, nausea, respiratory depression and dysphoria, is reportedly lower compared to other opioids [2]. Due to these characteristics, it has become one of the most popular opioid analgesics for use in cats in many countries [9, 10]. A recent clinical study, however, did illustrate that cats undergoing ovariohysterectomy may require a second dose of buprenorphine 4 h after surgery [11].…”
Section: Introductionmentioning
confidence: 99%
“…Current practice for most elective surgery, including canine OH, is to give a non‐steroidal anti‐inflammatory drug (NSAID), such as meloxicam, perioperatively (Hunt et al . ). Ideally, it should be given preoperatively for the bitch to benefit from “pre‐emptive analgesia” (Lascelles et al .…”
mentioning
confidence: 97%